DEEP LEARNING LEARNING STRATEGY TO IMPROVE STUDENTS' CRITICAL THINKING SKILLS IN PAI-BP LEARNING IN GRADE 6 OF STATE ELEMENTARY SCHOOL 081 PANYABUNGAN - Suaimah Suaimah; Arafatul Soraya; Yenni Asrifah; Riska Suaibah (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2026)
This study aims to examine the implementation of deep learning strategies and their role in developing critical thinking skills in sixth-grade Islamic Religious Education and Character Education (PAI-BP) in sixth-grade students at SD Negeri 081 Panyabungan. The background of this research is based on the continued dominance of lecture- and memorization-oriented PAI-BP learning, which has not optimally developed higher-order thinking skills, particularly critical thinking. However, the Independent Curriculum demands meaningful, student-centered learning and encourages the development of higher-order thinking skills. This study employed a qualitative approach with a descriptive qualitative approach. Subjects included PAI-BP teachers and sixth-grade students. Data collection techniques included observation, interviews, and documentation. Data analysis was conducted interactively through the stages of data reduction, data presentation, and conclusion drawing. Data validity was maintained through triangulation of sources and techniques. The results indicate that the deep learning strategy was implemented through the use of contextual problems, focus group discussions, open-ended questions, and reflection activities at the end of the lesson. The implementation of this strategy was able to create a more active, dialogic, and meaningful learning environment. Furthermore, students' critical thinking skills are beginning to develop, demonstrated by their ability to ask questions, analyze religious issues, justify opinions, and draw conclusions based on Islamic values. However, the implementation of this strategy still faces challenges such as limited learning time and differences in student abilities...